Environmental Impact Assessment of Municipal Solid Waste (MSW) Management in Florence, Italy - Masella, Piernicola; Guerrini, Lorenzo; Angeloni, Giulia; Parenti, Alessandro (European Journal of Sustainable Development, 2018)
Facing the trouble of municipal solid waste (MSW) management is a rising challenge of urbanized areas. Yearly data of waste management from the city of Florence (Italy) and neighboring municipalities were gathered over 2015 year. About 412105 t of waste were collected, where 202794 t were mixed-waste and 72540 t were organic. Fractions were treated in a centralized selecting-composting plant. The outgoing materials were further treated in external plants for additional selection, composting, incineration, landfilling. The present study was aimed to assess the environmental impact of such waste management applying LCA technique. The functional unit was “one year mixed and organic waste treatment at Florence and neighboring municipalities”. System boundaries included waste collection, final transport, working of the selecting-composting plant. System expansion was used to account for energy recovery (electricity) from waste. Background data were sourced from ELCD-core3-LCI database. Life cycle impact assessment (classification and characterization) was performed by ILCD midpoint method. Sixteen impact categories were computed. Focusing on global warming potential (GWP), the functional unit impacts for roughly 6.99E+8kgCO2eq. This figure drops to 0.212E+8kgCO2eq if urban collection was not considered and further to 0.186E+8kgCO2eq if final transportation was excluded. Results underline the potential benefit of on-site treatment of waste. Keywords: urban waste, landfilling, biogas, incineration, LCA, global warming potential